Ochratoxin A upregulates biomarkers associated with hypoxia and transformation in human kidney cells. (June 2019) - Raghubeer, Shanel; Nagiah, Savania; Chuturgoon, Anil
Abstract: Cellular adaptation to hypoxia is controlled by hypoxia-inducible factor 1α (HIF1α), a transcription factor activated in response to oxygen tension, reactive oxygen species (ROS) and inflammation. Overexpression of HIF1α and HSP90 has been associated with cancer induction. Ochratoxin A (OTA), a mycotoxin contaminant of food and beverages, has been linked to renal tumours and progressive nephropathies, inflammation and pro-oxidation. The aim of this study was to examine the effect of OTA on hypoxic and transformative regulators in human embryonic kidney (HEK293) cells. We evaluated the protein expression of HIF1α, HSP90 and PDK1 (western blotting), mRNA expression of HIF1α, VEGF, EPO and TGFβ (qPCR), and ATP levels (luminometry) in HEK293 cells exposed to a range of OTA concentrations (0.125 μM–0.5 μM) over two time periods (24 h and 48 h). After 24 h, OTA increased HIF1α protein ( p < 0.005) and EPO gene expression ( p < 0.05), while VEGF and TGFβ was significantly increased at 48 h. We also observed a correlation between PDK1 expression and ATP levels. In conclusion, OTA disrupts hypoxia regulation, modulates metabolic activity, and alters growth signalling ( VEGF, TGFβ ), which may lead to tumourigenesis. Highlights: HIF1α protein expression was upregulated by OTA (24 h; 0.125 μM). Gene expression of VEGF and TGFβ was increased by OTA (48 h) in HEK293 cells. Gene expression of EPO was increased by OTA at 24 h and 48 h. PDK1 expression was increased at 24 h and decreased at 48 h by OTA.